Az értékesítés digitális átalakulása: Az egyéni és szervezeti technológiaelfogadást meghatározó tényezők empirikus elemzése - Pelsőci, Balázs Lajos; Nagy, Ákos; Gáti, Mirkó (Vezetéstudomány / Budapest Management Review, 2021)
This study explores the digital transformation occurring within the sales industry. The authors formulate a theoretical model, built upon the Technology Acceptance Model (TAM) and the Technology Readiness Index (TRI), which also incorporates literature focusing on the tools and activities of the sales industry. Their model is based on an empirical study conducted in 2018, involving interviews with 112 different sales representatives. This research identified several factors affecting the digital transformation of the sales industry and pinpoints the interaction between these factors. The most important conclusion to be drawn is that technological readiness, the attributes of technology, the portfolio of activities, and the customer base all influence individual attitudes and, ultimately, affect acceptance. Nevertheless, they find it important to highlight the limitations of the study arising from their methodology and the extreme heterogeneousness of their sample, which make further analyses and tests of their theoretical model necessary.